THE TRANSFORMATIVE POWER OF ART IN ENGLISH LANGUAGE LEARNING - Abduvalieva Jasmina Jahongir qizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract: The integration of art in the teaching and learning of English language skills has emerged as a topic of growing significance in the field of education. This article explores the multifaceted ways in which artistic expression can profoundly enhance the acquisition and mastery of the English language. By examining the innate connection between art and language, the article highlights how engaging students in artistic pursuits can foster the development of vocabulary, critical thinking skills, creativity, and self-expression – all of which are essential elements in the journey of language learning. Furthermore, the article delves into the impact of art on student motivation and engagement, emphasizing its role in creating a dynamic and enriching learning environment that nurtures the holistic development of students. The findings of this article underscore the transformative power of art in the English language classroom and its potential to revolutionize the way we approach language education in the 21st century.